Conocimiento del personal de enfermería sobre bioseguridad en la manipulación de agentes citostáticos en el Hospital Vicente Rodriguez Witt Solca - Loja. - Tambo Morocho, María Liliana (2013)
The bioseguridad in labor terms is related with measures to protect to / the worker / to whose focus is bound with the risks in the manipulation of cytostatic agents. Nowadays the chemotherapy is recognized at the present time like one of the therapeutic main alternatives during the treatment of the cancer, the mutagenicidad properties, teratogenicidad, carcinogenicidad and local irritation of the cytostatic medications make fundamental the adaptation of measures of prevention and personal security during its manipulation (preparation, administration, accidental exhibition and disposition of residuals and wastes); this fact bears to a parallel increment of the risk for the health of those / ace workers / ace that manipulates them like he/she is the infirmary personnel, doctors and other professionals of the health, during the treatment that concerns the oncological patient. The present investigation work is of descriptive type whose purpose is to determine the grade of knowledge and to identify the application of bioseguridad measures in the manipulation of cytostatic agents of the Hospital Vicente Rodríguez Witt Solca-Loja. The method of gathering of data was through a survey and an observation (it lists of comparison) guide. The basic data gathered in the development of the investigation reveal that the professional personnel's 65% is among the ages from 25 to 35 years, and its watering citotóxico is high in relation to the time of more experience to 7 years of work in chemotherapy service, the same one that is related with bigger presence of local (pruritus, migraine, odinofagia, disfagia) effects and systemic (chromosomal fragility) effects; 65% has a level of knowledge half envelope the bioseguridad measures and handling of cytostatic, the execution level in its majority is incorrect with 50%. The results of the present investigative work, allowed to outline recommendations and to elaborate a handling guide of cytostatic to prevent and to diminish the labor risks for manipulation of cytostatic.